Les politiques et les pratiques en matière correctionnelle adulte au Québec : 1960-1985 - Gauthier, Maurice (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1986)
To proceed with an account and evaluation of the policies and practices in adult corrections in Quebec from 1960 to 1985 is to cover the period when the most spectacular reforms took place. The article points out that it is only since 1969 that Quebec has a centralized correctional sector under the authority of a director general. Before this date it was the sheriff who, in each of the territorial divisions in which he worked, assumed all correctional responsibility, by law, without any common philosophical basis. Quebec having proceeded with the construction of its adult correctional system step by step, by means of five year plans, the study of the assessment and evaluation of its policies and practices is divided into five year periods. This method has the advantage of furnishing the reader with a detailed view of the entire ascending progression of the correctional sector from 1960 to 1985, as well as its strengths and weaknesses. Above all, it gives the reader an understanding of the philosophical trends that guided its establishment and describes the principal actors and circumstancial events whereby, in the 1980's, the sector has come to function according to a unity of thought, and in a context of complimentarity with the other agencies of the criminal justice system.